The Polish version of the Emotion Regulation Questionnaire-Short Form (ERQ-S): Psychometric properties, Polish norms and relationships with psychopathology and well-being - Paweł Larionow; Karolina Mudło-Głagolska; David A. Preece (Cambridge Prisms: Global Mental Health)
The Emotion Regulation Questionnaire-Short Form (ERQ-S) is a brief 6-item self-report measure of two emotion regulation strategies, cognitive reappraisal and expressive suppression. It is a short form of the most widely used emotion regulation measure in the field, but currently there are limited data on the performance of the ERQ-S. The aim of this study was to introduce a Polish version of the ERQ-S, examine its psychometric properties and provide Polish norms to aid score interpretation. Our sample was 574 Polish-speaking adults aged 18–69 from the general community in Poland. We examined the ERQ-S’s factor structure and measurement invariance with confirmatory factor analysis. We assessed the concurrent validity of the questionnaire via relationships with psychopathology symptoms and well-being. As expected, the Polish version of the ERQ-S demonstrated strong factorial validity with a theoretically congruent 2-factor structure (cognitive reappraisal and expressive suppression factors), which was invariant across gender, age and education categories. The ERQ-S’s concurrent validity and internal consistency reliability were good. As expected, cognitive reappraisal was significantly associated with lower psychopathology symptoms and higher well-being, whereas the opposite pattern was present for expressive suppression. Overall, the Polish version of the ERQ-S has strong psychometric properties and good clinical relevance.